Efficacy of erector spinae plane block for postoperative pain management: A meta-analysis and trial sequential analysis of randomized controlled trials - Gonçalves, João Pedro Fernandes; Duran, Manuela Lopes; Barreto, Eduardo Silva Reis; Antunes Júnior, César Romero; Albuquerque, Luiz Gustavo; Lins-Kusterer, Liliane Elze Falcão; Azi, Liana Maria Torres de Araujo; Kraychete, Durval Campos (Journal of clinical anesthesia, 2025)
Postoperative pain remains a major problem across a wide range of surgical procedures. The efficacy and clinical utility of the Erector Spinae Plane Block (ESPB) in reducing postoperative pain remains uncertain. To evaluate the efficacy and safety of the ESPB compared with placebo or sham block in perioperative pain management. We searched PubMed, Embase, Web of Science, Scopus, and Cochrane CENTRAL for randomized controlled trials (RCTs) comparing ESPB to placebo or sham block in surgical patients. Primary outcomes included postoperative pain at 2 h, 6 h, 24 h, and 48 h, intraoperative and cumulative postoperative opioid consumption (24 h), and postoperative nausea and vomiting, pruritus, and block-related adverse events. Subgroup and sensitivity analyses, as well as meta-regressions, were performed to explore sources of heterogeneity. Trial sequential analysis (TSA) was used to assess the quantitative robustness of the available data. This review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) under registration number CRD42024583633. Forty-three RCTs were included, with 1361 patients randomized to the Erector Spinae Plane Block group. ESPB reduced postoperative pain at 2 h (MD −1.46;95 % CI −1.98 to −0.94;p < 0.001;I2 = 91 %), 6 h (MD −1.23;95 % CI −1.64 to −0.83;p < 0.001;I2 = 89 %), 24 h (MD −0.47;95 % CI −0.67 to −0.28;p < 0.001;I2 = 78 %), and 48 h (MD −0.24;95 % CI −0.39 to −0.09;p = 0.002;I2 = 10 %). Also, intraoperative opioid consumption (MD -137.43 μg;95 % CI −208.73 to −66.13;p < 0.001;I2 = 100 %), 24 h cumulative opioid consumption (MD −25.62 mg;95 % CI −31.31 to −19.93;p < 0.001;I2 = 99 %), and incidence of postoperative nausea and vomiting (RR 0.56;95 % CI 0.44 to 0.72;p < 0.001;I2 = 16 %) were significantly lower in patients submitted to ESPB. No significant differences were found in postoperative pruritus (RR 0.62;95 % CI 0.35 to 1.10;p = 0.105;I2 = 27 %). Notably, no block-related adverse events were reported in any study. Certainty of evidence was rated as low to moderate for most outcomes. TSA suggested that no further trials are needed to assess ESPB efficacy in the analyzed outcomes, except for postoperative pruritus. ESPB is a safe and effective regional anesthesia technique that significantly reduces postoperative pain and opioid consumption across various surgical procedures. •ESPB reduced postoperative pain at 2, 6, 24, and 48 h.•Intraoperative opioid and postoperative opioid consumption were lower in ESPB patients.•ESPB reduced postoperative nausea and vomiting.•ESPB was safe, with no block-related adverse events reported.•Trial sequential analysis suggest sufficient data is available on ESPB efficacy.